Santé au travail et discrétion des rapports sociaux - Carla Barros-Duarte; Marianne Lacomblez (Perspectives Interdisciplinaires sur le Travail et la Santé)
Current public health concerns highlight the little attention being paid to the effects of people’s occupational activity and related working conditions on their well-being, regardless of the amount of research being carried out in this area.The present study challenges all the dynamics which, by reinforcing one another, reproduce themselves, thus keeping the effects of the people’s work on the evolution of their health hidden from society.Starting within the framework of the contemporary scientific tradition of work psychology and ergonomics, the present study has underlined the interest in conceiving an intervention model situated at the public action level, particularly the regional level.